2018
DOI: 10.1021/acsmacrolett.7b00891
|View full text |Cite
|
Sign up to set email alerts
|

Triggerable Multivalent Glyconanoparticles for Probing Carbohydrate–Carbohydrate Interactions

Abstract: Carbohydrate–carbohydrate interactions are proposed to be biologically significant but have lower affinities than the well-studied carbohydrate–protein interactions. Here we introduce multivalent glyconanostructures where the surface expression of lactose can be triggered by an external stimulus, and a gold nanoparticle core enables colorimetric signal outputs to probe binding. Macromolecular engineering of a responsive polymer “gate” enables the lactose moieties to be presented only when an external stimulus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 40 publications
1
31
0
Order By: Relevance
“…For example, compared to monovalent carbohydrate ligands, linear polymers presenting carbohydrate subunits along their backbone can increase avidity up to a 1000‐fold . Several groups established additional types of multivalent scaffolds to improve carbohydrate binding, for example, 2D‐surfaces, nano‐ or microparticles, branched polymers, or dendrimers . Usually these systems were designed for a specific purpose, for example, to bind certain receptor molecules or organisms.…”
Section: Effect Of Ligand Presentation On the Affinity Of Carbohydratmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, compared to monovalent carbohydrate ligands, linear polymers presenting carbohydrate subunits along their backbone can increase avidity up to a 1000‐fold . Several groups established additional types of multivalent scaffolds to improve carbohydrate binding, for example, 2D‐surfaces, nano‐ or microparticles, branched polymers, or dendrimers . Usually these systems were designed for a specific purpose, for example, to bind certain receptor molecules or organisms.…”
Section: Effect Of Ligand Presentation On the Affinity Of Carbohydratmentioning
confidence: 99%
“…Other work on thermosensitive materials for the switchable presentation of carbohydrates used grafted polymers on nanoparticles or 2D surfaces . Typically, these systems were able to capture and release carbohydrate binding proteins upon temperature change, but the successful release of bacteria was not yet confirmed, probably due to the strong adhesion and additional entanglements of the fimbriae .…”
Section: Switchable Carbohydrate Presenting Scaffoldsmentioning
confidence: 99%
“…Glycopolymers (Man-1) 4 , (Man-2) 4 , (Man-3) 4 , and (Man-5) 4 are sequence-controlled multiblock copolymers with two strictly alternating blocks, one Man bearing binding block and one hydrophilic spacing block (Figure 1, bottom). The Man-presenting block of a glycopolymer has the same sequence as its oligomeric relative (Man-1, Man-2, Man-3, and Man-5) which is then incorporated four times in average within the polymer sequence.…”
Section: Glycooligomer and Glycopolymer Synthesismentioning
confidence: 99%
“…Given the low affinity of protein–carbohydrate interactions, it is important to design multivalent carbohydrates exhibiting biologically relevant interaction to protein receptors. Researchers have established various types of scaffolds presenting sugars for high‐affinity binding, for example, 2D surfaces, microgels, nanoparticles, hydrogel beads, dendrimers, or polymers . Due to the low affinity and comparatively short lifetime of single carbohydrate–protein complexes, carbohydrates presented on polymeric scaffolds (glycopolymers) predominantly show an additive, “statistical” contribution when binding to receptors .…”
Section: Introductionmentioning
confidence: 99%
“…Previous research into using sugar‐lectin targeting for drug delivery has shown that presenting the targeting sugar in a high concentration, such as that on the surface of a particle, increases the targeting efficiency of a drug delivery vector, taking advantage of the “glycocluster effect.” Recent developments in this area have applied the principle of targeting lectins with glycopolymers in more refined systems, using sequenced defined polymers alone and in combination with stimuli responsive polymers to elicit a more specific biological targeting . Among the many stimuli responsive systems reported, poly( N ‐isopropylacrylamide) is commonly used for temperature response, where heating above the cloud point of the system triggers a self‐assembly or reveals a glycopolymer . Next to temperature, pH is arguably one of the most ubiquitously exploited stimuli, used to induce polymer assembly and disassembly, or to release a covalently bound drug molecule via an acid cleavable linker; these among many other unique systems represent a growing and active field of research in drug delivery …”
Section: Introductionmentioning
confidence: 99%